Mitochondrial Acetylation and Diseases of Aging - Gregory R. Wagner; R. Mark Payne (Journal of Aging Research)
In recent years, protein lysine acetylation has emerged as a prominent and conserved regulatory posttranslational modification that is abundant on numerous enzymes involved in the processes of intermediary metabolism. Well-characterized mitochondrial processes of carbon utilization are enriched in acetyl-lysine modifications. Although seminal discoveries have been made in the basic biology of mitochondrial acetylation, an understanding of how acetylation states influence enzyme function and metabolic reprogramming during pathological states remains largely unknown. This paper will examine our current understanding of eukaryotic acetate metabolism and present recent findings in the field of mitochondrial acetylation biology. The implications of mitochondrial acetylation for the aging process will be discussed, as well as its potential implications for the unique and localized metabolic states that occur during the aging-associated conditions of heart failure and cancer growth.